Sugar-Derived Amidines and Congeners: Structures, Glycosidase Inhibition and Applications - Blériot, Yves; Auberger, Nicolas; Désiré, Jérôme (Current Medicinal Chemistry, 2022)
Glycosidases, the enzymes responsible for the breakdown of glycoconjugates, including di-, oligo- and polysaccharides, are present across all kingdoms of life. The extreme chemical stability of the glycosidic bond combined with the catalytic rates achieved by glycosidases makes them among the most proficient of all enzymes. Given their multitude of roles in vivo, inhibition of these enzymes is highly attractive with potential in the treatment of a vast array of pathologies ranging from lysosomal storage and diabetes to viral infections. Therefore great efforts have been invested in the last three decades to design and synthesize inhibitors of glycosidases leading to a number of drugs currently on the market. Amongst the vast array of structures that have been disclosed, sugars incorporating an amidine moiety have been the focus of many research groups around the world because of their glycosidase transition state-like structure. In this review, we report and discuss the structure, the inhibition profile, and the use of these molecules, including related structural congeners as transition state analogs.
Keywords: transition state